Analisis Yuridis Perlindungan Hukum terhadap Pasien dalam Kasus Tindak Pidana Malpraktek Menurut Undang-Undang No. 29 Tahun 2004 tentang Praktik Kedokteran - Siregar, Gomgom T.P. (ARBITER: Jurnal Ilmiah Magister Hukum, 2023)
The high level of crime, including medical malpractice, demands legal protection for patients. The diversity of crimes involving professional classes makes detection and handling increasingly complex. Medical malpractice is often difficult for law enforcement to detect due to challenges in proving negligence or intent. In a legal context, a crime occurs when someone's actions harm or victimize others. Medical malpractice involves a doctor's actions that deviate from operational standards. Consequences include civil and criminal legal sanctions. Responsibilities, including ethical, public, and civil aspects, are associated with medical malpractice. Differences in sanctions and medical risks are emphasized in both medical laws and ethics. Sanctions for medical malpractice are regulated by the Medical Practice Act and the Code of Medical Ethics. Malpractice involves elements of intentional wrongdoing or negligence, while medical risks are not criminal offenses. Medical accidents occur unpredictably and cannot be blamed. Legal protection for patients is crucial in responding to various challenges in the healthcare field.